Experience with Floating Interbank Exchange Rate Systems in Five Developing Economies - Galbis, Vicente (IMF Working Papers; Working Paper ;, 1993)
This paper reviews the experience with floating interbank exchange rate systems in five developing countries--The Gambia, Guyana, Jamaica, Nigeria and Sri Lanka--and draws some conclusions about the stability and efficiency of these systems. The experience of these countries illustrates both the difficulties and the advantages of interbank exchange rate markets. The main conclusion is that these markets can operate relatively well with a minimum banking infrastructure, provided that the authorities remove legal and institutional impediments to the free operation of these markets including, in particular, exchange restrictions. Any residual restrictions that may remain will likely give rise to the continued existence of parallel markets.